Analisis dan Implementasi SAK EMKM Pada UMKM Kopi Ndeso - Surya Anjani; Lukman Anthoni (Prisani Cendekia, 2023)
The accounting standard used by UMKM in the preparation of financial statements is SAK EMKM. Existing constraints such as resources and the lack of knowledge of the existing SAK EMKM provisions for UMKM have become a separate phenomenon and become the task of the government, including academics, so that they can disseminate information to the public. Problem identification still relies on general ledgers and Microsoft Excel as monthly and annual income and expense reports and has not recorded income in accordance with SAK EMKM standards. The formulation of the problem in this study is that the recording of sales at Kopi Ndeso and the presentation of financial statements have not adjusted the provisions of SAK EMKM. Kopi Ndeso's UMKM have not made accounting records based on SAK EMKM because there is also no supervision or assistance from parties with an interest in UMKM financial reports, especially the government, regulators and other interested institutions or entities. Suggestions that can be given to Kopi Ndeso UMKM are that in the future they can continue to develop their businesses and increase knowledge and awareness about the field of UMKM and learn how to prepare financial reports in accordance with SAK EMKM